Phenotypic plasticity plays an essential role in the confrontation between plants and herbivorous insects - Xianzhong Wang; Jieyu Kang; Huizhong Wang; Shigui Wang; Bin Tang; Jiangjie Lu (CABI Agriculture and Bioscience)
Abstract The interaction between insects and plants is a classic case of coevolution. During the arms race that has continued for 400 million years, the mutualistic (such as pollination and defense assistance) and antagonistic relationships gradually formed and complicated under the selection pressure from phytophagous insects. Thus, plants have developed diverse defense strategies, constantly balancing the relationship between defense and growth. At the same time, insects have evolved the ability to adapt to and resist plant defenses. Throughout this process, phenotypic plasticity has continuously helped both groups adapt to new environments and niches. Epigenetic changes play an important role in the formation of plastic phenotype. These changes allow parental defense traits to be passed on to the offspring, helping the offspring resist insect feeding. Epigenetic changes and genetic variation provide the basis for the formation of new phenotypes, and plants can form stable defense traits under long-term insect feeding pressure. In this review, we summarize the defense strategies of plants and the counter-defense strategies of insects, suggest that phenotypic plasticity plays an important role in this interaction, and discuss the role of epigenetics in the formation of plastic phenotypes.